As the gods stand akimbo: aberrations of post-independence nationalist politics in Wole Soyinka’s Kongi’s harvest - Javangwe, Tasiyana D. (Unisa Press, 2016)
This article explores the inherent contradictions of nationalist consciousness that are manifested at different historical stages of Africa’s struggle for liberation from colonialism. Analysing Wole Soyinka’s Kongi’s harvest (1967), the article argues that nationalism, which effectively focuses the cultural resources of the subjugated Africans against the common white enemy during the liberation struggle, becomes highly problematic the moment that common enemy is removed. Fractures emerge in the imagination of the new nation as the. captains of the new nation adopt a narrow perspective of nationhood that seeks to place the ruling elite or the all-powerful leader at the centre of the nation’s cultural life. In Soyinka’s Kongi’s harvest, such a narrow perspective is depicted throiigh attempts to de-legitimate traditional symbols of power, the invention of new but superficial cultural repertoires that are meant to give false impressions of national progress, as well as acts of self-glorification by the leadership.Thus, the postcolonial dispensation is characterised by absurd aberrations of nationalist politics that translate into a moral economy of violence that is visited on the citizenry.